2021
DOI: 10.3390/polym13040608
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in UHMWPE/UHMWPE Nanocomposite/UHMWPE Hybrid Nanocomposite Polymer Coatings for Tribological Applications: A Comprehensive Review

Abstract: In the recent past, polymer coatings have gained the attention of many researchers due to their low cost, their ability to be coated easily on different substrates, low friction and good anti-corrosion properties. Various polymers such as polytetrafluroethylene (PTFE), polyether ether ketone (PEEK), polymethylmethacrylate (PMMA), polyurethane (PU), polyamide (PA), epoxy and ultra-high molecular weight polytheylene (UHMWPE) have been used to develop these coatings to modify the surfaces of different components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…Ti-6Al-4V is of very common use in orthopedics, given its excellent mechanical properties, corrosion resistance and good biocompatibility [38]. In the same field, UHMWPE is one of the most widely used materials for the bearing surface of prostheses in hip replacement, sometimes with adequate functionalization to overcome limitations related essentially to wear debris [39]. PEEK has emerged over the years as a promising material for prostheses, partially due to its ability to be processed using additive manufacturing techniques [40,41].…”
Section: Materials Tested and Their Surfacesmentioning
confidence: 99%
“…Ti-6Al-4V is of very common use in orthopedics, given its excellent mechanical properties, corrosion resistance and good biocompatibility [38]. In the same field, UHMWPE is one of the most widely used materials for the bearing surface of prostheses in hip replacement, sometimes with adequate functionalization to overcome limitations related essentially to wear debris [39]. PEEK has emerged over the years as a promising material for prostheses, partially due to its ability to be processed using additive manufacturing techniques [40,41].…”
Section: Materials Tested and Their Surfacesmentioning
confidence: 99%
“…Nowadays, there is a growing interest in membrane formation from ultra-high molecular weight polyethylene (UHMWPE). The latter (in comparison to conventional polyethylenes (PE)) has a higher mechanical strength [14], abrasion resistance [15], impact viscosity [16], and a greater puncture Membranes 2023, 13, 422 2 of 21 strength [17], which is a very important property for separators of Li-ion batteries. The literature analysis performed earlier [18] showed that UHMWPE membranes were mainly obtained by the sintering of powders [19] and thermally induced phase separation (TIPS) [20], including its combination with stretching [21].…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports of limited successful outcomes for UHMWPE reinforced with MWCNTs [ 18 , 21 , 22 ]. Although, there is still a disagreement related to the biocompatibility of CNT at the present time, because some researchers investigated their cytotoxicity [ 23 , 24 , 25 ], while other authors reported that CNTs are considered as perfect substrates for cellular development [ 26 , 27 ].However, it is a well-accepted fact that CNTs and multi-walled CNTs with multi-walls i.e., MWCNTs have induced an intense interest for a number of industrial applications including the biomaterials, sensors, catalyst supports, and energy storage devices mainly because of their physical and mechanical characteristics [ 28 , 29 , 30 ]. It has been described in literature that significant features for the characterization of MWCNTs are surface properties, imperfection sites, and graphitization [ 31 ].Numerous techniques are employed in order to achieve MWCNTs with optimized properties.…”
Section: Introductionmentioning
confidence: 99%